2003
DOI: 10.1128/jvi.77.15.8366-8377.2003
|View full text |Cite
|
Sign up to set email alerts
|

Circulation of Endemic Type 2 Vaccine-Derived Poliovirus in Egypt from 1983 to 1993

Abstract: From 1988 to 1993, 30 cases of poliomyelitis associated with poliovirus type 2 were found in seven governorates of Egypt. Because many of the cases were geographically and temporally clustered and because the case isolates differed antigenically from the vaccine strain, it was initially assumed that the cases signaled the continued circulation of wild type 2 poliovirus. However, comparison of sequences encoding the major capsid protein, VP1 (903 nucleotides), revealed that the isolates were related (93 to 97% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
260
1
14

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(283 citation statements)
references
References 62 publications
8
260
1
14
Order By: Relevance
“…Serotypes 1, 2 and 3 of wild-type PVs have been reported to recombine with each other (Dahourou et al, 2002;Furione et al, 1993). Wild-type and OPV strains have been reported to recombine (Dahourou et al, 2002;Georgescu et al, 1995;Guillot et al, 2000;Liu et al, 2000Liu et al, , 2003Yang et al, 2003) and PVs have been shown to recombine with serotypes of HEV-C (Brown et al, 2003;Jiang et al, 2007;Rousset et al, 2003). Furthermore, vaccine-derived PV strains, defined as having more than 1 % nucleotide differences in the VP1 protein coding region (reviewed recently by Agol, 2006;Kew et al, 2004), have been reported to have an interserotypic recombinant genome (Blomqvist et al, , 2004Martin et al, 2002) as well as a recombinant genome with a non-structural region from an unknown HEV-C strain (Arita et al, 2005;Kew et al, 2002Kew et al, , 2004Rakoto-Andrianarivelo et al, 2008;Rousset et al, 2003;Shimizu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Serotypes 1, 2 and 3 of wild-type PVs have been reported to recombine with each other (Dahourou et al, 2002;Furione et al, 1993). Wild-type and OPV strains have been reported to recombine (Dahourou et al, 2002;Georgescu et al, 1995;Guillot et al, 2000;Liu et al, 2000Liu et al, , 2003Yang et al, 2003) and PVs have been shown to recombine with serotypes of HEV-C (Brown et al, 2003;Jiang et al, 2007;Rousset et al, 2003). Furthermore, vaccine-derived PV strains, defined as having more than 1 % nucleotide differences in the VP1 protein coding region (reviewed recently by Agol, 2006;Kew et al, 2004), have been reported to have an interserotypic recombinant genome (Blomqvist et al, , 2004Martin et al, 2002) as well as a recombinant genome with a non-structural region from an unknown HEV-C strain (Arita et al, 2005;Kew et al, 2002Kew et al, , 2004Rakoto-Andrianarivelo et al, 2008;Rousset et al, 2003;Shimizu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, numerous examples have shown that mutations in the 59UTR markedly decrease multiplication efficiency (Willian et al, 2000), alter cell tropism (Shiroki et al, 1997) and attenuate virulence (Tu et al, 1995;DeJesus et al, 2005). Moreover, recombination can occur in the 59UTR (Adu et al, 2007;Yang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, numerous examples have shown that mutations in the 59UTR markedly decrease multiplication efficiency (Willian et al, 2000), alter cell tropism (Shiroki et al, 1997) and attenuate virulence (Tu et al, 1995;DeJesus et al, 2005). Moreover, recombination can occur in the 59UTR (Adu et al, 2007;Yang et al, 2003).The enterovirus coding region, divided into three subregions (P1-P3), encompasses a single ORF encoding a single polyprotein. The P1 region encodes four structural proteins (VP4, VP2, VP3 and VP1), whilst the nonstructural proteins are encoded in the P2 (2A, 2B and 2C) and P3 (3A, 3B, 3C and 3D polymerase) regions.…”
mentioning
confidence: 99%
“…Therefore, OPV recipients usually excrete altered vaccine viruses after vaccination (3). Acquired alterations in the base sequence of the altered vaccine viruses may change their degree of attenuation (5) as well as, their temperature sensitivity(ts) (2). All the three Sabin strains are temperature-sensitive, producing lower virus yields at supra-optimal temperatures than the wild poliovirus (6).…”
Section: Introductionmentioning
confidence: 99%
“…This is usually the case for wild poliovirus infection. However some live-attenuated vaccine polioviruses that have re-acquired wild-like properties following replication in human gut also show neurovirulence like the wild strains (2) and are excreted by oral polio vaccine (OPV) recipients (3).…”
Section: Introductionmentioning
confidence: 99%